Simplifying equations is often the first step to solving algebra equations.

Some methods that can be used to simplify an equation are Combine Like Terms, Multiplication & Division of Terms, Removal of Brackets (Distributive Property) and Cross Multiplication.

Some methods that can be used to simplify an equation are Combine Like Terms, Multiplication & Division of Terms, Removal of Brackets (Distributive Property) and Cross Multiplication.

Like terms are terms that have the same variable part i.e. they only differ in their coefficients. Combining like terms is very often required in the process of simplifying equations.

For example:

2*x* and –5*x* are like terms

*a* and are like terms

6*x* and 5*y* are unlike terms

Like terms can be added or subtracted from one another.

For example:

*a* + *a* = 2 × *a* = 2*a* (We usually write 2 × *a* as 2*a*)

2*a* + 4*a* = 6*a*

*a + a + a* = 3*a *

2*a* + 4 (Unlike terms cannot be simplified)

4*a* + 3*b* (Unlike terms cannot be simplified)

6*a* – 3*a* = 3*a*

8*b* – 8*b* = 0

5*a* – 3 (Unlike terms cannot be simplified)

6*a* – 4*b* (Unlike terms cannot be simplified)

Simplify: 8*xy* – 5*yx* = 1

Solution:

Step 1: 5*yx* is the same as 5*xy *using the commutative property

Step 2: Since the right side is already simple, we can work on the left side expression:

8*xy* – 5*yx* = 8*xy* – 5*xy* = 3*xy*

Putting back the left side and right side of the equation:

3*xy* = 1

Answer: 3*xy* = 1

Example 2:

Simplify: 7*a* + 5*b* – 6*b* + 8*a* + 2*b* = 0

Solution:

Step 1: Group together the like terms:

7*a* + 5*b* – 6*b* + 8*a* + 2*b* = 0

(7*a* + 8*a*) + (5*b* – 6*b* + 2*b*) = 0

Step 2: Then simplify:

15*a* + *b* = 0

Answer: 15*a* + *b* = 0

The coefficients and variables of terms can be multiplied or divided together in the process of simplifying equations.

For example:

3 × 4*b* = 3 × 4 × *b* = 12*b*

5*a* × 3*a* = 5 × *a* × 3 × *a* = 5 × 3 × *a* × *a* = 15*a*^{2} (using exponents)

Beware! | a × a = a^{2} |

a + a = 2a |

Example 1:

Simplify: 4*a* × 5*a* ÷ 2*a* = 60

Solution:

Step 1: Perform the multiplication and division

Step 2: Isolate variable *a *

Answer: *a* = 6

Sometimes removing brackets (parenthesis) allows us to simplify the expression. Brackets can be removed by using the distributive property. This is often useful in simplifying equations.

For example:

3(*a* – 3) + 4 = 3 × *a* + 3 × (-3) + 4 = 3*a* – 9 + 4 = 3*a* – 5

5 – 6 (*b* + 1) = 5 + ( – 6 ) × *b* + (– 6) × 1 = 5 – 6*b* – 6 = – 6*b* – 1

Example 1:

Simplify: 5(*a* – 4) + 3 = 8

Solution:

Step 1: Remove the brackets

5*a* – 20 + 3 = 8

Step 2: Isolate variable *a *

5*a* = 8 – 3 + 20

5*a* = 25

Answer: *a* = 5

Cross multiplication allows you to remove denominators from fractions in an equation. Note that this technique applies only towards simplifying equations, not to simplifying expressions.

For example, if you have the equation:

then you can multiply the numerator of one fraction with the denominator of the other fraction (across the = sign) as shown:

to obtain the equation

(2 × 6) = *a* × 3

Example 1:

Simplify:

Solution:

Step 1: Cross Multiply

4 × *a* = 8 × 5

4*a* = 40

Step 2: Isolate variable *a *

Answer:* a* = 10

Rotate to landscape screen format on a mobile phone or small tablet to use the **Mathway** widget, a free math problem solver that **answers your questions with step-by-step explanations**.

You can use the free Mathway calculator and problem solver below to practice Algebra or other math topics. Try the given examples, or type in your own problem and check your answer with the step-by-step explanations.

We welcome your feedback, comments and questions about this site or page. Please submit your feedback or enquiries via our Feedback page.